Safe at Home with Assistive Technology - Kollak, Ingrid (Springer International Publishing : Imprint: Springer, 2017)
This book describes how assistive technology can help handicapped, elderly and acutely sick people to manage their daily lives better and stay safe in the home. It discusses how safety is understood from an ethical, technical and social perspective, and offers examples of the problems that users, their helpers and professional carers have with assistive technology in everyday situations. The book provides insights from user-centred research and uses photographs to illustrate the main topic: how users and technology can work together to ensure safety. User-focused and combining experience with research, the book will interest users of these kinds of technology, health professionals who might introduce and/or prescribe them, engineers who develop and sell assistive technological gadgets, and architects who build safe homes - as well as researchers and students who work in these fields. It provides an overview of the existing technology, examines ways to test its effectiveness from the point of view of users, health professionals and researchers from different fields (architecture, education, engineering, facility management, medicine, nursing, occupational therapy, rehabilitative medicine, physiotherapy, social science and speech therapy), and lists useful addresses, websites and literature.
Keywords: Medicine.; Geriatric nursing.; Rehabilitation.; Occupational therapy.; Physiotherapy.; Biomedical engineering.; Health economics.; Medical economics.; elektronické knihy; electronic books